Exploring trust in religious leaders and institutions as a mechanism for improving retention in child malnutrition interventions in the Philippines: a retrospective cohort study. Issue 9 (2nd September 2020) - Lau, Lincoln Leehang; Dodd, Warren; Qu, Han Lily; Cole, Donald C
Abstract : Objectives: In the context of persistent child malnutrition in the Philippines, the objective of this study was to examine how different dimensions of trust affected programme retention and physiological outcomes when a faith-based organisation (FBO) addressed moderate and severe acute malnutrition among children from households experiencing extreme poverty. Setting: We retrospectively analysed survey data collected by International Care Ministries (ICM) in 2012–2013 across 150 communities in eight provinces (Negros Oriental, Negros Occidental, Bohol, Palawan, Sarangani, South Cotabato, Sultan Kudarat and Zamboanga del Norte) of the Philippines. Study participants: Caregivers of 1192 children experiencing moderate acute malnutrition and severe acute malnutrition between the ages of 6 and 60 months. Intervention: A 16-week child malnutrition treatment programme called Malnourished Child Outreach offered by ICM in partnership with local religious leaders and institutions. Primary and secondary outcome measures: Programme dropout and weight-for-height z-score (WHZ) at the end of the programme for enrolled children were the two outcomes of interest. A logistic mixed-effects model was built to assess factors associated with programme dropout and a linear mixed-effects model for factors associated with WHZ at the end of the programme. Results: Trust in religious leaders or institutions (−0.87 (95% CI: −1.43, –0.26)) was negatively associated with programme dropout, suggesting that with increasing levels of trust, decreasing proportions of children dropped out of treatment. Retention in the programme led to improved WHZ among participating children (−0.38 (95% CI: −1.43, 0.26)). Various measures of social capital, including trust in religious and public institutions, were not associated with WHZ at the end of the programme. Conclusions: Leveraging pre-existing trust in religious leaders and institutions among households experiencing extreme poverty is one way that ICM, and potentially other FBOs, can promote retention in child nutrition interventions among vulnerable populations.